Comparative in vitro activities of twelve antimicrobial agents against Campylobacter species. - Fliegelman, R M (1985)
The in vitro susceptibility of 27 Campylobacter jejuni, 31 Campylobacter coli, and 30 Campylobacter fetus subsp. fetus strains to 12 antimicrobial agents was determined. Ciprofloxacin, a new quinoline derivative, was the most active agent tested. Antimicrobial susceptibility differed among the three species tested.